Two new species of Hypostomus suckermouth-armoured catfishes (Teleostei: Loricariidae) from central Brazil - Soares, Yan F. F.; de Aquino, Pedro De Podestà Uchôa; Bagley, Justin C.; Langeani, Francisco [UNESP]; Colli, Guarino R. (Wiley, 2021)
This study describes two new endemic Hypostomus species from central Brazil, which were previously identified as genetically distinct lineages in a recent genomic study that recommended their testing and potential description based on morphological data. A machine learning classification procedure (random forest) was used to investigate morphological variation and identify putatively diagnostic characters for these candidate species and revealed that each is morphologically distinct. The new species Hypostomus cafuringa is characterized by small size, dark spots under a light background, deeper caudal peduncle and shorter first ray of the pectoral fin and base of the dorsal fin when compared to congeneric species from the region. H. cafuringa is known from the headwaters of the Maranhão River, upper Tocantins River basin, Distrito Federal, Brazil. The second new species, Hypostomus crulsi, is characterized by dark spots under a light background, absence of plates along the abdomen region, shorter first ray of the pelvic fin, shorter first ray of the pectoral fin and smaller body size. H. crulsi is known from the headwaters of the São Bartolomeu River, upper Paraná River basin, Distrito Federal, Brazil. The rapid conversion of natural habitats for agricultural development and the isolation of protected areas represent a serious threat to the continued existence of these two newly described endemic species, which warrant conservation assessment.
Keywords: Hypostominae; Neotropical fishes; Siluriformes; taxonomy